Pediatric immunization-related safety incidents in primary care: A mixed methods analysis of a national database. Issue 32 (31st July 2015) - Rees, Philippa; Edwards, Adrian; Powell, Colin; Evans, Huw Prosser; Carter, Ben; Hibbert, Peter; Makeham, Meredith; Sheikh, Aziz; Donaldson, Liam; Carson-Stevens, Andrew
Abstract Background Children are scheduled to receive 18–20 immunizations before their 18th birthday in England and Wales; this approximates to 13 million vaccines administered per annum. Each immunization represents a potential opportunity for immunization-related error and effective immunization is imperative to maintain the public health benefit from immunization. Using data from a national reporting system, this study aimed to characterize pediatric immunization-related safety incident reports from primary care in England and Wales between 2002 and 2013. Methods A cross-sectional mixed methods study was undertaken. This comprised reading the free-text of incident reports and applying codes to describe incident type, potential contributory factors, harm severity, and incident outcomes. A subsequent thematic analysis was undertaken to interpret the most commonly occurring codes, such as those describing the incident, events leading up to it and reported contributory factors, within the contexts they were described. Results We identified 1745 reports and most (n = 1077, 61.7%) described harm outcomes including three deaths, 67 reports of moderate harm and 1007 reports of low harm. Failure of timely vaccination was the potential cause of three child deaths from meningitis and pneumonia, and described in a further 113 reports. Vaccine administration incidents included the wrong number of doses (n = 476, 27.3%), wrong timing (n = 294, 16.8%), and wrong vaccine (n = 249, 14.3%). Documentation failures were frequently implicated. Socially and medically vulnerable children were commonly described. Conclusion This is the largest examination of reported contributory factors for immunization-related patient safety incidents in children. Our findings suggest investments in IT infrastructure to support data linkage and identification of risk predictors, development of consultation models that promote the role of parents in mitigating safety incidents, and improvement efforts to adapt and adopt best practices from elsewhere, are needed to mitigate future immunization-related patient safety incidents. These priorities are particularly pressing for vulnerable patient groups.